Preconception Health Behaviors of Low-Income Women. Issue 5 (September 2016) - Ayoola, Adejoke B.; Sneller, Krista; Ebeye, Tega D.; Dykstra, Megan Jongekrijg; Ellens, Victoria L.; Lee, HaEun Grace; Zandee, Gail L.
Abstract: Purpose: Preconception behaviors have a significant impact on birth outcomes, particularly among low-income minority groups, and women with unplanned pregnancies. This study examined women's perceived health status and behaviors such as drinking, smoking, exercise, and use of multivitamins and folic acid. Study Design and Methods: This was a descriptive study based on a convenience sample of women living in urban underserved neighborhoods. Univariate and bivariate analyses were conducted using STATA 13. Results: The sample consisted of 123 women ages 18 to 51 years (mean = 30.57); 51.22% were Hispanic, 36.59% African American, and 12.2% Caucasian. Over 70% had a household income of less than $20, 000, 57.72% had no health insurance in the last year, and 58.54% were not married. These women were below the Healthy People 2020 goals for drinking, smoking, and multivitamin use, especially those who were planning to get pregnant in the next 6 months or not sure of their pregnancy planning status. There were no significant differences on any of the preconception health behavior variables based on pregnancy intention. Clinical Implications: Nurses and healthcare providers should emphasize importance of practicing healthy behaviors during the preconception period among low-income ethnic minority women specifically those living in urban medically underserved areas who are unsure of their pregnancy planning status or are at risk of unintended pregnancy. Abstract : Women of childbearing age who are at risk of becoming pregnant do not always practice health promoting behaviors. As many pregnancies are unintended, all women of childbearing age could benefit from support and encouragement from nurses to be as healthy as they can by taking multivitamins and folic acid, avoiding smoking, and maintaining a healthy weight through a balanced diet and moderate activity.